PENGARUH VOLUME LUMPUR AKTIF DAN WAKTU KONTAK TERHADAP PENURUNAN KADAR BOD LIMBAH CAIR RUMAH SAKIT - idayu Kurniawati Estiningsih; Mifbakhuddin - (JURNAL LITBANG, 2007)
Bsckground:BOD is the quality of oxygen in the solution bacterial/micro organism, needs to do decomposition aerobic from the organic materials in the standart time condition and specific clinical term. process system of the waste water treqtment is the most ffictive do BOD descent is process biologic system which using the activated sludge. Production of waste water with the SBR System (Sequince Batch Reactor) very effective to waste water production, because just using a wash tab for the oli process. The fist material is the octivated sludge in the process and time interaction have ifto th'e processing product of the hospital waste water.Obiective :To explain the effect of the activated sludge and time interaction BOD descent hospital waste water.Research Methode :This research is explanatory research kinds the research is the true experiment and the pre tesl - post test plan with control design . Subject research is hospilal waste water from waste water treqtment department. Sample random sampling with the total somple 500 ml for the one experiment andfor five replication need 75 experiment. This fi'ee variable research is the activaled sludge volume and iime interaction and variable attacted is BOD descent hospital waste water. The Analyse with descriptive and analyse which use onova test ond we trust 95o%.Result:BOD descent highestfor activated sludge volume 250 ml/ lfor the time interaction minute l5 mirute is 99,5 % . Wilh the anova test one factor we know that a factor level differences variation every experiment group is sludge volume and time interaction is very dffirent with the score p = 0,000. Andthen with anova test interaction with the two factor we know have relationship with significan between level activated sludge concentration and long interaction time in BOD descent hospital waste waterscore p : 0,000. Statistic style test which use it explain the level BOD descent hospital waste water 96,67 %Conclution :Activated sludge volume ond long time interaction have effect to the BOD descent hospital wsqte wqter, for pH condition 7,96.. Activated sludge volume 250 ml/l and time interactionl5 minute ffictive to BOD descent hospital waste water until 99,5%o.. To be dffirences significan between many level concentrqtion qctivated sludge and long time interaction.Kev Word :Activated sludge volume, time interaction, BOD commend descent hospital waste water.